Co-movement of stock exchange indices and exchange rates in Ghana: A wavelet coherence analysis - Peterson Owusu Junior; Baidoo Kwaku Boafo; Bright Kwesi Awuye; Kwame Bonsu; Henry Obeng-Tawiah (Cogent Business & Management, 2018)
By means of the Continuous Morlet Wavelet Transform fostering covariance/correlation, lead-lag causal relationship as well as coherency via the wavelets analysis, we explore the two indices on the Ghana Stock Exchange, the larger Ghana Stock Exchange Composite Index (GSE-CI) and the smaller Ghana Stock Exchange Financial Services Index (GSE-FSI) with the US dollar and Euro. Using daily data from January 2011 to December 2016 we confirm that there is mixed interplay of lead-lag relationships, mostly strong at lower frequencies, among the indices and the two most important exchange rates in Ghana. This paper serves as the first of its kind in the literature owing to its rich methodology and variables employed. Our study implies that investing selectively in either GSE-CI or GSE-FSI is very important and differences in co-movement of GSE-CI and GSE-FSI with the exchange rates. We reveal that there is narrowly identifiable lead-lag relationship between GSE-CI and USD/GHS and GSE-FSI and USD/GHS. Investors as revenue maximisation agents should consider the time and frequency spaces of the GSE-CI and GSE-FSI in their investment decisions involving diversification with the USD and EUR both in the short- and medium-terms (up to four years). Further, any policy meant to influence performance on the Ghana Stock Exchange should consider the time and frequency domains of the equities traded on the exchange.
Keywords: 650